2009
DOI: 10.1038/onc.2008.458
|View full text |Cite
|
Sign up to set email alerts
|

FEN1 contributes to telomere stability in ALT-positive tumor cells

Abstract: Abrogation of telomere stability through loss-of-function mutations in telomere binding proteins contributes to genomic instability and cancer progression. Recently, Flap endonuclease 1 (FEN1) was shown to contribute to telomere stability in human cells that had not yet activated a telomere maintenance mechanism, suggesting that abrogation of FEN1 function influences the transformation process by compromising telomere stability and driving genomic instability. Here, we analyse the telomeres in human cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Cell Culture-All cells were grown as reported (25)(26)(27)(28). Briefly, cells were grown at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Culture-All cells were grown as reported (25)(26)(27)(28). Briefly, cells were grown at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Virus Production and Infection-Lentiviral production and cell infections were carried out as described (25,26,29). Briefly, 293T cells were transfected with TransIT-LT1 (Mirius, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rad52, which interacts with Rad51, forms a heptameric ring that binds single-stranded DNA ends and catalyzes the DNA-DNA interaction necessary for the annealing of complementary strands (39,40). Recent studies have demonstrated that other proteins, including flap endonuclease 1 (FEN1), MUS81, the Fanconi anaemia group D2 (FANCD2) and Fanconi anaemia group A (FANCA) are also significant for ALT mechanisms (41)(42)(43). These proteins are significant in telomere maintenance, as shown by previous studies (44,45).…”
Section: A B C Dmentioning
confidence: 99%
“…1-3 Several factors either not directly involved in HR or having multiple functions are also essential for ALT telomere maintenance, for example the flap endonuclease FEN1 18 and the single ss DNA binding protein RPA. 19 The long noncoding RNA 'telomeric repeat-containing RNA' (TERRA), a DNA-dependent RNA polymerase II transcript produced from chromosome ends, 20,21 is emerging as a novel feature associated to ALT.…”
mentioning
confidence: 99%